(Re)existência e protagonismo etnoambiental: aspectos do processo de reterritorialização de comunidades quilombolas de Virgem da Lapa, no Médio Jequitinhonha - Adília Jardim Silva (2020)
The Jequitinhonha Valley has, among its communities, Campinho and Capim Puba, analyzed here, that were expropriated from their common land - the domains of plateaus -, in a process initiated in the 1970s, for the generalized planting of eucalyptus, a source supply chain for the steel industry. It is worth mentioning that the residents domiciled there did not have the titles of dominance, which legally characterized these lands as vacant, that is, Union lands. In the official discourse, forestry in these lands would represent the development for Vale, considered as Vale da “Misery” and “poverty”. However, in the process of implementing such enterprises, the singularity of the local population and the management of natural resources traditionally practiced without environmental degradation were disregarded. That said, this work essentially aims to understand the processes of deterritorialization of the communities of Campinho and Capim Puba directly associated with the implementation of monoculture eucalyptus and their socio-environmental implications to discuss, next, the current context of the process of reterritorialization and " sociogeobiodiversidade ". To this end, it was intended to understand how the implementation of this economic activity took place, seeking, in parallel, to elucidate the processes of deterritorialization and reterritorialization of communities, and, also seeking to better understand the relationship between agricultural management, its relationship with biodiversity and the effects of forestry on these practices. For that, we started from the phenomenological method, with the adoption of the category of analysis Territory. The following methodological procedures were adopted as a way of operationalizing the investigation: bibliographic survey; semi-structured meetings and interviews; participant observation and transversal walk to better understand the vision, representations and relationships established, by such communities, with the Territory.